Invasive candidiasis in a Brazilian neonatal intensive care unit - Henrique Yuji Watanabe Silva; Felipe Teixeira de Mello Freitas (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to describe the epidemiology of invasive candidiasis in a neonatal intensive care unit. Methods: cross-sectional study that included all neonates with invasive candidiasis confirmed by blood culture from April 2015 to June 2018. Demographic, clinical and microbiological data were analyzed, comparing neonates with extreme low birth weight (ELBW) with neonates ≥ 1000g birth weight, considering a p <0.05 as statistically significant. Results: there were 38 cases of invasive candidiasis, resulting in an overall incidence of 2.5%. Twelve (32%) were ELBW neonates and 26 (68%) neonates ≥ 1000g birth weight, an incidence of 4.4% and 2.0%, respectively. Abdominal surgery was more frequent among neonates with birth weight ≥ 1000g compared to ELBW neonates (85% vs. 17%; p <0.01), as well as the median in days of antibiotics use (18 vs. 10.5; p = 0.04). The median in days of mechanical ventilation was more frequent among ELBW neonates (10 vs. 5.5; p = 0.04). The majority of Candida species were non-albicans (64%). Fatality rate was 32%. Conclusions: the incidence of invasive candidiasis among neonates with birth weight ≥ 1000g was higher than that found in the literature. This group has a higher proportion of gastrointestinal malformations that require surgery. Thus, fluconazole prophylaxis may be necessary for a broader group of neonates.